A Previously Unrecognized Granulomatous Variant of Gamma-Delta T-Cell Lymphoma - Tatsiana Pukhalskaya; Bruce R. Smoller; David M. Menke; Olayemi Sokumbi (MDPI AG, 2021)
Primary cutaneous γδ T-cell lymphoma (PCGD-TCL) is an extremely rare and aggressive T-cell neoplasm with complex heterogeneity. We present a series of two patients who presented with firm, subcutaneous nodules and were diagnosed with PCGD-TCL. In both cases, biopsies demonstrated a both superficial and deep adnexotropic infiltrate comprised of angiocentric, medium- to large-sized atypical lymphocytes. The infiltrate extended into the panniculus. Immuno-histochemical stains highlighted atypical lymphocytes that expressed CD3, CD8 and CD56 but were negative for EBV ISH. A brisk histiocytic response with focal aggregation into granulomas was highlighted with a PG-M1 stain. The atypical lymphocytes were positive for gene rearrangements on a TCR delta stain and negative for βF-1. CT and PET scan in one of the two patients demonstrated diffuse, subcutaneous, ground-glass foci; hypermetabolic soft tissue nodules; and lymphadenopathy in the lungs, as well as splenomegaly. A diagnosis of histiocyte-rich PCGD-TCL was rendered. A histiocyte-rich, granulomatous variant of γδ T-cell lymphoma is extremely rare. Its potentially misleading resemblance to inflammatory granulomatous conditions could pose a diagnostic pitfall in this already challenging condition. This variant may resemble granulomatous mycosis fungoides and granulomatous slack skin syndrome, but it has a distinct, aggressive clinical outcome.